Employee quality, monitoring environment and internal control - Chunli Liu; Bin Lin; Wei Shu (China Journal of Accounting Research, 2017)
We investigate the effect of internal control employees (ICEs) on internal control quality. Using special survey data from Chinese listed firms, we find that ICE quality has a significant positive influence on internal control quality. We examine the effect of monitoring on this result and find that the effect is more pronounced for firms with strict monitoring environments, especially when the firms implement the Chinese internal control regulation system (CSOX), have higher institutional ownership or attach greater importance to internal control. Our findings suggest that ICEs play an important role in the design and implementation of internal control systems. Our study should be of interest to both top managers who wish to improve corporate internal control quality and regulators who wish to understand the mechanisms of internal control monitoring.
Keywords: 650; Employee; Internal control; Monitoring; Human capital